2020
DOI: 10.1155/2020/1508258
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors for Fractures in Patients with Type 2 Diabetes over 60 Years Old: A Cross-Sectional Study from Northeast China

Abstract: Aims. Previous evidence has demonstrated an increased fracture risk among the population with type 2 diabetes mellitus (T2DM). This study investigated the prevalence of bone fractures in elderly subjects (with and without type 2 diabetes) and identified any fracture risk factors, especially the risk factors for common known fractures in particular diabetic populations. Methods. This cross-sectional study was conducted with community-dwelling people over 60 years old in nine communities from the city of Shenyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…It is controversial about the relationship between diabetes and BMD. Some studies suggest that there is no significant difference in lumbar BMD between diabetes mellitus patients and normal glucose tolerance group in the elderly [ 17 , 18 ], while some study report an increase in BMD in patients with diabetes [ 19 ]. In the present study, postmenopausal women with T2DM over 65 years old have higher BMD than those without diabetes, significant differences were observed, which is not consistent with some previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…It is controversial about the relationship between diabetes and BMD. Some studies suggest that there is no significant difference in lumbar BMD between diabetes mellitus patients and normal glucose tolerance group in the elderly [ 17 , 18 ], while some study report an increase in BMD in patients with diabetes [ 19 ]. In the present study, postmenopausal women with T2DM over 65 years old have higher BMD than those without diabetes, significant differences were observed, which is not consistent with some previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of fractures in patients with senile T2DM in China is 7.3%, and the decrease in BMD is one of the independent risk factors of fractures [ 19 ]. Serum vitamin D level plays a crucial part in bone metabolism by promoting the absorption of calcium and phosphorus to maintain stable blood calcium and phosphorus concentrations and promoting bone mineralization, stimulating osteoblasts to promote bone formation and inhibit osteoblast apoptosis, and promoting the differentiation of precursor osteoclasts into mature osteoclasts and promoting bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that elderly DM patients are more predisposed to osteoporosis and chronic cardiopulmonary diseases [ 12 , 13 ]. According to statistics, the prevalence of osteoporosis in elderly T2DM patients is as high as 31.7%, which seriously hinders the normal life activities of such patients and greatly affects patients' as well as their families' quality of life [ 14 ]. Therefore, optimizing nursing methods is of great significance for improving the outcome and quality of life of elderly DM patients.…”
Section: Discussionmentioning
confidence: 99%